Antenatal Screening for Postpartum Depression - Maliha Sadaf, Farzana Kazmi, Sobia Nawaz Malik , (Journal of Rawalpindi Medical College, 2011)
Background: To identify the risk factors for postnatal depression in antenatal patients and to detect the progression of depressive symptoms in postnatal period. Methods:In this descriptive study, 150 pregnant women were screened at booking antenatal visit for Antenatal Depression (AND) and also for risk factors with regard to Postnatal Depression (PND). Patients having hypertension, diabetes, thyroid problem were excluded from the study. PND was assessed at 4 – 6 weeks postpartum by Edinburgh Postnatal Depression Scale. Results :AND and PND were identified in 10% and 12.67% of the women respectively. All the women (100%) with AND in the current pregnancy and having past-psychiatric history developed PND. 60% of the women with previous history of AND and 90.90% of those having history of PND developed PND in current pregnancy. PND was found to be more common in low socio-economic group and in nulliparous women. Conclusion:Antenatal focus on the proper screening of the risk factors may help to identify women at risk of postpartum depression.